Effect of proline in comparison to PVS2 in cryopreservation of somatic embryo and callus cultures of date palm (Journal of Biodiversity Conservation and Bioresource Management, 2023)
In this work, the amino acid proline was investigated as cryoprotectant in cryostorage of date palm, Phoenix dactylifera L., tissue cultures. Among various levels of proline, it was found that 15% is the most effective one on survival. This concentration was compared to Plant Vitrification Solution 2 (PVS2). Generally, the maximum viability percentages of the two types of cryoprotectants were registered at 60 min exposure period. Proline was superior to PVS2 on callus viability. Moreover, healthy and good appearance calli were observed with the proline treatments. In contrast, the highest viability percentages of somatic embryos were observed with PVS2 solution. Regarding regrowth, the recovery parameters of both callus and somatic embryos increased as exposure period increased till 60 min and then decreased. The maximum callus fresh mass and growth value were registered when callus was cryoprotected by 15% proline. With respect to somatic embryos, proline gave good differentiation percentages, but they were slightly lower than PVS2. The highest differentiation percentage (70%) was recorded with PVS2 for 60 min in cryoprotection. However, the highest numbers of proliferated shootlets were recorded with proline in cyoprotection.Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 11-20